Lactobacillus spp. E Bifidobacterium sp. atenuam a mucosite intestinal experimental induzida por 5-fluorouracil em camundongos - Quaresma, Marielle Pires (2016)
Intestinal Mucositis is a higher adverse effects of treatment with 5-fluorouracil. In this context, probiotics are widely used to protect gastrointestinal disorders. Here we report the effect Probiotil® composed by probiotics Lactobacillus acidophilus and Bifidobacterium lactis, and Probiatop® composed by Lactobacillus acidophilus, Lactobacillus paracasei, Lactobacillus rhamnosus and Bifidobacterium lactis in intestinal mucositis induced by 5-FU. Such methodology was used male Swiss mice (25-30g), treated with a single intraperitoneal dose by 5-FU (450 mg / kg ip), and controls with(saline and DMSO). In the Probiotics groups was administrated Probiotil® or Probiatop® 1h, 24h and 48h (V.O.) after induction by 5-FU . 72h after 5-FU administration, mice was euthanized. Segments from Duodenum, jejunum and ileum were removed for evaluations: measurement of villous / crypt ratio; Histological scores; concentration of glutathione (GSH), malondialdehyde (MDA), proinflammatory cytokines (TNF-α and IL-6) activity and myeloperoxidase (MPO). In addition, we investigated the weight analysis, leukogram, gastric emptying and intestinal transit of animals. Our results showed that Probiatop® decreased the weight loss induced by 5-FU, but Probiotil® did not change weight loss. The probiotics had no effect on leukopenia but both probiotics were capable of reverting changes in three intestinal segments (duodenum, jejunum and ileum), such as increased GSH levels (except the ileum), decreased MDA levels, indicating a reduction oxidative stress. The probiotics decreased TNF-α and IL-6 levels, neutrophils infiltration, reducing the inflammatory response. The relationship villus / crypt was reversed, demonstrating intestinal mucosal protection. Probiotics did not show a significant reversal of histological scores. The delayed gastric emptying was reversed by Probiatop® but not by Probiotil®. However, there was no effect of probiotics on the intestinal transit changes. In conclusion, Probiotil® and Probiatop® protected the intestinal mucosa from antioxidant and anti-inflammatory activities. However, only Probiatop® reversed gastric emptying.